Mapping of international trade liberalization and trade balance position in developing country - Hairani, Tuti, Iskandar Ali Alam, Singagerda, Faurani Santi, (Opción, 2019)
This research intends to explore the impact of tariff elimination on Indonesian Trade Balance. The GTAP model was used as the main tool of analysis. The findings show that the elimination of the tariff barrier will result in a decrease in a large part of Indonesian exports either for agricultural export or for manufactured export. In conclusion, the implementation of tariff elimination policy will cause the trade balance for some commodities to experience deficits, especially for some strategic commodities in the agricultural sector, and overall manufacturing.